Archival Theory, Chronology and Interpretation of Rock Art in the Western Cape, South Africa - Mguni, Siyakha (Cambridge Monographs in African Archaeology Ser., 2017)
This book advocates the archival capacity of rock art and uses archival perspectives to analyse the chronology of paintings in order to formulate a framework for their historicised interpretations.